Radiographical post-operative flexion gap balance was improved using a modified gap-balancing technique in navigation-assisted total knee arthroplasty - Toyooka, Seikai; Leeyaphan, Jirapong; Masuda, Hironari; Nishihara, Nobuhiro; Miyamoto, Wataru; Kawano, Hirotaka; Nakagawa, Takumi (Journal of Arthroscopy and Joint Surgery, 2020)
Adequate lower extremity alignment and knee joint stability are important factors in total knee arthroplasty (TKA) for achieving good prognosis after surgery. There is still controversy surrounding the best technique for TKA. Although several reports have compared the measured resection technique with the gap-balancing technique, little is known about the flexion gap difference after cruciate-retaining (CR) TKA. This study aimed to compare radiographic images of post-operative flexion gap balance after CR TKA using the navigation-assisted measured resection (NAMR) technique and the navigation-assisted modified gap-balancing (NAMGB) technique. A total of 70 patients with knee osteoarthritis underwent CR TKAs (28 NAMR procedures, 42 NAMGB procedures). Flexion gap balance was compared by measuring the lift-off angle (LOA), which was the angle between the tibial cutting line and the posterior condylar axis, on axial radiographs of the distal femur at 3 months post-operatively. Furthermore, post-operative hip-knee-ankle (HKA) angles, range of motion (ROM), and Knee Society Score (KSS) were compared between the two groups. The mean post-operative LOA in the NAMGB group was significantly lower than that in the NAMR group (1.2 ± 1.7° varus versus 2.3 ± 2.7° varus; p < 0.05). No difference in post-operative HKA angle, ROM, or KSS was observed. Based on post-operative axial radiographs of the distal femur, post-operative flexion balance was better in the NAMGB group after CT TKAs. We believe that the NAMGB technique provides better soft-tissue balancing than NAMR TKA.